The Prevalence of Helicobacter pylori Infection in Bleeding and Non -Bleeding Gastric Ulcers: A Cross-Sectional Case-Control Study - (:unkn) unknown (My University, 2016)
Introduction: Helicobacter pylori is a known and important cause of peptic ulcer disease, and can result in many different complications, both gastrointestinal and systemic. The gastric complications include upper gastrointestinal bleeding. The costs associated with testing and treatment of complications of H. pylori infection is also high, both in private and public setting. Studies in Iran showed high prevalence of H. pylori infection, with figures as high as 89.2% in the adult population. In South Africa, patients with bleeding gastric ulcers receive empirical eradication therapy, an expensive practice in a resource limited country like South Africa. It is for this reason that we conducted a case-control study to determine the difference in prevalence of H. pylori infection in bleeding and non-bleeding gastric ulcers. Aim: To determine the difference in prevalence of H. pylori infection in bleeding and non-bleeding gastric ulcers. Methods: In this prospective cross-sectional case-control study, a total of 173 patients who underwent upper endoscopy at Steve Biko Academic Hospital were recruited. All patients with gastric ulcer on upper endoscopy had antral mucosal biopsy taken and CLO test done on this specimen, in addition to the CLO test, the 42 with a history of upper gastrointestinal bleeding had additional biopsies send for histology for detection of H. pylori. The CLO tests were evaluated 24 h later and results documented as either positive or negative. Results: From the 173 patients enrolled, 131 patients were found to have no history of upper gastrointestinal bleeding, while 42 patients were found to be bleeding on upper endoscopy or had a recent history of bleeding. Of the total of 173, 134(77.5%) tested negative for H. pylori infection on CLO test and 39(22.5%) tested positive. Of the bleeding group, 7(16.7%) were CLO test positive and 35(83.3%) were negative. In the non-bleeding group of patients, 99(75.6%) were CLO test negative and 32(24
Keywords: African Research